The Demand for Services in India. A Mirror Image of Engel's Law for Food? - Nayyar, G (Department of Economics (University of Oxford), 2009)
India’s development experience over the past fifty years suggests that the increasing importance of the services sector deserves analysis. The literature on structural change has emphasised changing patterns of demand as an explanation for the increasing importance of the services sector. In order to establish the significance of private final demand as an explanation for the increasing importance of the services sector in India, this paper estimates Engel curve-type relationships for six categories of services: education, health, entertainment, personal, communication and transport. In doing so, it uses Tobit and censored quantile regressions to analyse household survey data in 1993-94 and 2004-05. We find upward sloping Engel curves which implies that there is a consistent increase in the household budget share allocated to services in the aggregate and to each individual services category as total household expenditure increases. This is a powerful explanation for the increasing share of the services sector.